Holy Angels and Economy of Christ - Nikolov, Danail (Forum Theologicum Sardicense, 2025)
Danail Nikolov, Holy Angels and Economy of Christ. The Holy An-gels play an important role in the Economy of Christ. Despite the incomparable significance of their mission, angels play a subordinate role in the economy of salvation. Jesus Christ is the Savior of the human race, and angels have an auxiliary function, serving and obeying Him. This is evident from numerous passages in the Scriptures. Not only has God appointed angels as helpers and associates in human salvation, but He has also assigned each believer a guardian angel. Information about guardian angels is found in both the Old and New Testaments. The Fathers of the Orthodox Church maintain that the primary mission of guardian angels is to assist every Christian in the work of salvation, faith, and godliness. Guardian angels protect us and safeguard our souls and bodies from both visible and invisible enemies (demons), and their care and intercession before God are of particular importance.